Validity and reliability of criterion based clinical audit to assess obstetrical quality of care in West Africa - Pirkle Catherine M; Dumont Alexandre; Traore Mamadou; Zunzunegui Maria-Victoria (BMC, 2012)
Abstract Background In Mali and Senegal, over 1% of women die giving birth in hospital. At some hospitals, over a third of infants are stillborn. Many deaths are due to substandard medical practices. Criterion-based clinical audits (CBCA) are increasingly used to measure and improve obstetrical care in resource-limited settings, but their measurement properties have not been formally evaluated. In 2011, we published a systematic review of obstetrical CBCA highlighting insufficient considerations of validity and reliability. The objective of this study is to develop an obstetrical CBCA adapted to the West African context and assess its reliability and validity. This work was conducted as a sub-study within a cluster randomized trial known as QUARITE. Methods Criteria were selected based on extensive literature review and expert opinion. Early 2010, two auditors applied the CBCA to identical samples at 8 sites in Mali and Senegal (n = 185) to evaluate inter-rater reliability. In 2010-11, we conducted CBCA at 32 hospitals to assess construct validity (n = 633 patients). We correlated hospital characteristics (resource availability, facility perinatal and maternal mortality) with mean hospital CBCA scores. We used generalized estimating equations to assess whether patient CBCA scores were associated with perinatal mortality. Results Results demonstrate substantial (ICC = 0.67, 95% CI 0.54; 0.76) to elevated inter-rater reliability (ICC = 0.84, 95% CI 0.77; 0.89) in Senegal and Mali, respectively. Resource availability positively correlated with mean hospital CBCA scores and maternal and perinatal mortality were inversely correlated with hospital CBCA scores. Poor CBCA scores, adjusted for hospital and patient characteristics, were significantly associated with perinatal mortality (OR 1.84, 95% CI 1.01-3.34). Conclusion Our CBCA has substantial inter-rater reliability and there is compelling evidence of its validity as the tool performs according to theory. Trial registration Current Controlled Trials ISRCTN46950658